THU0503 In-Vitro Supression of TH17 Responses in Inflammatory Arthritis Patients Using Small Molecule Ror-Gamma-T Inhibitors. (10th June 2014) - Al-Mossawi, M.H.; De Wit, J.; Huhn, M.; Ridley, A.; Bunting, H.; Arancibia, C.; Powrie, F.; Bowness, P.
Abstract : Background: Increasing evidence implicates the type 17 immune axis in the pathogenesis of inflammatory arthritidies including ankylosing spondylitis (AS), and targeting of the pathway in AS has shown benefit in early clinical trials 1 . Cells driving inflammation in this axis express the transcription factor retinoid-related orphan nuclear receptor gamma T (ROR-gt) and make the signature pro-inflammatory cytokine interleukin-17A (IL-17A) 2 . Digoxin, a small-molecule inhibitors of ROR-gt has proved successful in the treatment of mouse experimental autoimmune encephalomyelitis 3 but the dose needed to achieve inhibition in human cells is over 100 fold greater than the toxic threshold. New non-digoxin small molecule ROR-gt inhibitors have now been developed and we explore their role in the human inflammatory arthritidies. Objectives: To determine the effects of novel small molecule ROR-gT inhibitors on in-vitro peripheral blood derived Type 17 T cell responses of patients with inflammatory arthritis. Methods: Blood samples were obtained from patients with AS, rheumatoid arthritis (RA) and psoriatic arthritis (PsA). CD4 positive type 17 cells were expanded from peripheral blood monocuclear cells (PBMCs) of patients with inflammatory arthritis using low strength anti-CD2/3/28 stimulation and recombinant IL-2 in a 7 day culture system. Two different ROR-gt inhibiting compounds (A & B) were added at the start of the culture system and their effects on multiple cytokine expression (IL-17A, IFN-gamma, IL-22, GM-CSF, TNF-alpha) was determined by flow cytometry using intracellular staining. IL-17A production was validated using ELISA. Results: Both ROR-gt small molecule inhibitors resulted in a consistent decrease in the percentage of patient-derived IL-17A-producing CD4 T cells. Overall there was approximately a 50% reduction in IL-17A production in AS (n=24, p<0.0001. see fig). The inhibition of IL-17A was confirmed on ELISA. There was a similar level of inhibition observed in IL-17F production. IL-22/IL-17A double producing cells were also inhibited but there was no significant effect on IL-22 single producers (Th22 cells). The effects of these inhibitors seem to be specific to type-17 cytokines (IL-17A, IL-17F) since we did not observe significant effects on the total amounts of other measured cytokines (IFN-gamma, TNF-alpha, GM-CSF). We saw inhibition of IL-17A production in RA and PsA. ROR-gt compounds did not adversely affect cell viability or proliferation in our culture system. Conclusions: Our results demonstrate a consistent and specific inhibition of IL-17A responses from patient derived PBMCs using small molecule ROR-gt inhibitors. We believe these results provide a solid rationale for the testing of these compounds in clinical trials particularly in AS where the treatment options remain limited. References: Baeten, D. et al. Anti-interleukin-17A monoclonal antibody secukinumab in treatment of ankylosing spondylitis: a randomised, double-blind, placebo-controlled trial. The Lancet 382, 1705–1713 (23). Yang, X. O. et al. T Helper 17 Lineage Differentiation Is Programmed by Orphan Nuclear Receptors RORα and RORγ. Immunity 28, 29–39 (2008). Huh, J. R. et al. Digoxin and its derivatives suppress TH17 cell differentiation by antagonizing RORγt activity. Nature 472, 486–490 (2011). Acknowledgements: Inhibitor compounds and funding for research consumables was provided by Merck. Disclosure of Interest: : M. H. Al-Mossawi Grant/research support: Merck, J. De Wit Grant/research support: Merck, M. Huhn Grant/research support: Merck, A. Ridley: None declared, H. Bunting: None declared, C. Arancibia Grant/research support: Merck, F. Powrie Grant/research support: Merck, P. Bowness Grant/research support: Merck DOI: 10.1136/annrheumdis-2014-eular.1110